Nanoscale imaging of shale fragments with coherent X‐ray diffraction. Issue 6 (30th November 2020) - Chattopadhyay, Basab; Madathiparambil, Aldritt S.; Mürer, Fredrik K.; Cerasi, Pierre; Chushkin, Yuriy; Zontone, Federico; Gibaud, Alain; Breiby, Dag W.
Abstract : Combined coherent X‐ray diffraction imaging and wide‐angle X‐ray diffraction is demonstrated to study the morphology, internal structure and mineralogy of shale fragments. Estimates of the unconnected nanoscale pore structure of shale microparticles are obtained. Abstract : Despite the abundance of shales in the Earth's crust and their industrial and environmental importance, their microscale physical properties are poorly understood, owing to the presence of many structurally related mineral phases and a porous network structure spanning several length scales. Here, the use of coherent X‐ray diffraction imaging (CXDI) to study the internal structure of microscopic shale fragments is demonstrated. Simultaneous wide‐angle X‐ray diffraction (WAXD) measurement facilitated the study of the mineralogy of the shale microparticles. It was possible to identify pyrite nanocrystals as inclusions in the quartz–clay matrix and the volume of closed unconnected pores was estimated. The combined CXDI–WAXD analysis enabled the establishment of a correlation between sample morphology and crystallite shape and size. The results highlight the potential of the combined CXDI–WAXD approach as an upcoming imaging modality for 3D nanoscale studies of shales and other geological formations via serial measurements of microscopic fragments.